If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6y-(17)-10)=
We move all terms to the left:
(6y-(17)-10)-()=0
We add all the numbers together, and all the variables
(6y-27)-()=0
We add all the numbers together, and all the variables
(6y-27)=0
We get rid of parentheses
6y-27=0
We move all terms containing y to the left, all other terms to the right
6y=27
y=27/6
y=4+1/2
| 8.1x-2.2=38.3 | | 9(u+5)=81 | | 11=3p+2-6 | | x+95+x+63=136 | | 2d-8d=-(-5+d)+5(-d-3) | | 25y-35=5(5y-7) | | 12x-5=6-x | | x+95+x+63=196 | | 2x²-7x=5 | | 1/3(6x+24)-20=3x-18 | | 4x+2=6(x-8) | | 2-0.9h=2 | | 13h+7=-h | | 2(4×-3)=5x-27 | | 25x+37=5x-12 | | 5(m-20)=20 | | 12y+6=2(6y+3) | | x÷10=13 | | 8=3(3x-6 | | x/3+6=-15.3 | | -369=6(-11x+4)+3 | | 5x-8=-6x | | 0.5x-3=3.9x-20 | | -7+1/6x=5 | | 2.6=p/2 | | 7k-7(1-5k)=40-5k | | -8(5x-8)=264 | | j+3=−14 | | 6(2x+9)-(11x-4)=7 | | 3(500-a)+10a=3600 | | -3k-22-8k=11 | | 5.72x+19.34-2.42x=3.5x+12 |